Increased pupal temperature has reversible effects on thermal performance and irreversible effects on immune system and fecundity in adult ladybirds - Awde, David N; Řeřicha, Michal; Knapp, Michal (Communications biology, 2023)
The environmental conditions an organism encounters during development vary in their lasting impact on adult phenotypes. In the context of ongoing climate change, it is particularly relevant to understand how high developmental temperatures can impact adult traits, and whether these effects persist or diminish during adulthood. Here, we assessed the effects of pupal temperature (17 °C - normal temperature, 26 °C - increased temperature, or 35 °C - heat wave) on adult Harmonia axyridis thermal stress tolerance, immune function, starvation resistance, and fecundity. The temperature during pupation significantly affected all investigated traits in fresh adults. Heat acclimation decreased adult haemocyte concentration, cold tolerance, and total egg production, and had a positive effect on heat tolerance and starvation resistance. The negative effects of heat acclimation on cold tolerance diminished after seven days. In contrast, heat acclimation had a lasting positive effect on adult heat tolerance. Our results provide a broad assessment of the effects of developmental thermal acclimation on H. axyridis adult phenotypes. The relative plasticity of several adult traits after thermal acclimation may be consequential for the future geographic distribution and local performance of various insect species.
Keywords: brouci; aklimatizace; teplota; fertilita; Animals; Pupa; Acclimatization; Immune System; Temperature; zvířata; Fertility; kukla; imunitní systém; Coleoptera